Comprehensive Efforts Office of Religion In Handling Minor Marriages Post The Determination of Law No. 16 of 2019 Concerning Marriage - Wa Eva Musdalifah; Basri Basri; La Hanuddin (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
This research will be carried out using qualitative methods, by collecting data through observation, interviews and analysis of documentation from the KUA. The data analysis used is qualitative analysis. It is hoped that this research will provide an overview of the efforts made by the KUA to deal with the problem of underage marriage and the factors that influence it and provide recommendations for improving and developing the KUA's efforts in dealing with this problem. The comprehensive efforts of the KUA (Religious Affairs Office) in dealing with underage marriages follow the inclusion of various efforts to prevent and handle the problem of underage marriages in Law Number 16 of 2019 concerning Marriage. These steps include: (1) sensitization and education about the dangers and negative impacts of underage marriage for the parties involved, (2) increased coordination and cooperation with related parties such as families, schools and communities, (3) stricter inspections regarding documents required for the marriage process, (4) development of a supervision and monitoring system for marriages recorded at the KUA, and (5) strict sanctions for parties who violate marriage regulations.